The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/qute.202000063
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Amount of Single‐Qubit Rotations in VQE and Related Algorithms

Abstract: With the advent of hybrid quantum classical algorithms using parameterized quantum circuits, the question of how to optimize these algorithms and circuits emerges. In this paper, it is shown that the number of single-qubit rotations in parameterized quantum circuits can be decreased without compromising the relative expressibility or entangling capability of the circuit. It is also shown that the performance of a variational quantum eigensolver (VQE) is unaffected by a similar decrease in single-qubit rotation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…This question of circuit expressivity is an active area of research, see Refs. [22][23][24][25][26][27][28][29][30][31][32] and references therein. In particular, it has been proposed to assess the expressivity of a parametric quantum circuit by quantifying the circuit's ability to uniformly reach the full Hilbert space [23], which was accomplished by computing statistical properties based on randomly sampling states from a given circuit template.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This question of circuit expressivity is an active area of research, see Refs. [22][23][24][25][26][27][28][29][30][31][32] and references therein. In particular, it has been proposed to assess the expressivity of a parametric quantum circuit by quantifying the circuit's ability to uniformly reach the full Hilbert space [23], which was accomplished by computing statistical properties based on randomly sampling states from a given circuit template.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been proposed to assess the expressivity of a parametric quantum circuit by quantifying the circuit's ability to uniformly reach the full Hilbert space [23], which was accomplished by computing statistical properties based on randomly sampling states from a given circuit template. Using this ansatz, it has been shown that the number of single-qubit rotations in certain parameterized quantum circuits can be decreased without compromising the expressivity of the circuit [26]. On the other hand, it has been shown that the inclusion of redundant parametrized gates can make the quantum circuits more resilient to noise [29,32].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the initial circuit energy L(θ 0 ) that cannot differ much from the ensemble average (7), the energy L(θ τ ) at an intermediate time τ should significantly deviate almost by definition (27) of the steepest descent method. It indicates how distinctive the intermediate states |ψ(θ τ ) are from initial states, thus requiring independent exploration of their geometric properties.…”
Section: Optimization Trajectorymentioning
confidence: 99%
“…The curves in Figures 3a and 3b are respectively the energy gap ∆E and Renyi-2 entanglement entropy R (2) evaluated under an equal partitioning of n = 12 qubits. The blue/orange colors indicate whether the displayed values are before/after applying the gradient descent (27) to circuit parameters τ = 5000 times. When the average entanglement entropy of the pre-optimization states saturates to the maximum possible value, as the cases for p ≤ 0.1, Figure 3a exhibits the formulation of orange dot clusters around ∆E ∼ 9.…”
Section: A Circuit State Entanglementmentioning
confidence: 99%
See 1 more Smart Citation